2002
DOI: 10.1002/pat.324
|View full text |Cite
|
Sign up to set email alerts
|

Vibration damping materials based on interpenetrating polymer networks of carboxylated nitrile rubber and poly(methyl methacrylate)

Abstract: Interpenetrating polymer networks (IPNs) based on carboxylated nitrile rubber (XNBR) and poly(methyl methacrylate)s were synthesized. Crosslinked XNBR was swollen in methyl methacrylate containing benzoyl peroxide as initiator and tetraethylene glycol dimethacrylate as crosslinking agent. The compositions of the IPNs were varied by changing the swelling time of the rubber in the methacrylate monomer. The dynamic mechanical properties of the IPNs were studied. The dynamic mechanical properties in the range 1±10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…XNBR is polar, reactive polymer that exhibits good compatibility with polar or non-polar resins and higher degree of interaction with fillers 2 . It is also reported that XNBR has improved damping properties, showing a great potential as matrix polymers 3,4 . Since polymer are rarely used commercially in a pure state to modify some of their properties by the incorporation of various additives, such as fillers, vulcanizing agents, and plasticizers etc.…”
Section: Introductionmentioning
confidence: 95%
“…XNBR is polar, reactive polymer that exhibits good compatibility with polar or non-polar resins and higher degree of interaction with fillers 2 . It is also reported that XNBR has improved damping properties, showing a great potential as matrix polymers 3,4 . Since polymer are rarely used commercially in a pure state to modify some of their properties by the incorporation of various additives, such as fillers, vulcanizing agents, and plasticizers etc.…”
Section: Introductionmentioning
confidence: 95%
“…An effective way is to incorporate viscoelastic regions of several separate phases by using block copolymerization, [6] blending various polymers together, [7,8] preparing a polymer with laminated gradient properties, [9] or creating interpenetrating polymer networks (IPNS). [10,11] Another effective way is to prepare a polymer with a distribution of chemical structure, and hence with a range of thermal motions of the molecular segments, to widen the T g transition. [12] If a polymer possesses a gradual change in structure (termed 'gradient structure') its glass transition range should be broad, which will significantly expand its damping range.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the temperature range for efficient damping of known rubbers is about 20-30 °C around the glass transition temperature. The glass transition can be broadened or shifted by the use of plasticizers or fillers, blending, grafting, copolymerization, crosslinking, or the formation of interpenetrating polymer networks (IPNs) [7][8][9][10][11][12][13][14]. But it is hard to obtain a damping material with a high tan δ value and a wide temperature range for damping properties at the same time.…”
Section: Introductionmentioning
confidence: 99%